Antara Like dan Ridha Allah: Tantangan Moral dan Spiritual Remaja Muslim di Media Sosial: Between Likes and Allah's Pleasure: Moral and Spiritual Challenges of Muslim Teenagers on Social Media - Ananda Ayu Salsabila; Siti Nur Cahya Atika; Lilis Setyorini; Adella Cinta Hendriani (Litera Academica Publishing, 2025)
The development of social media platforms has changed the way Muslim teenagers form their identities, gain recognition from their communities, and express their religiosity. The phenomenon of seeking ‘likes’ as a form of digital recognition often conflicts with Islamic principles that emphasize sincerity, humility, and a life goal oriented towards pleasing Allah. In this study, researchers applied a Systematic Literature Review approach by analyzing 21 scientific articles related to adolescent digital behavior, religious identity, mental health, religious literacy, and Islamic ethics in the use of social media. The findings indicate that the culture of seeking likes can cause social pressure, anxiety, digital riya' (showing off), image competition, and a superficial understanding of religion. However, social media can also serve a positive function as a means of religious education, creative da'wah (proselytizing), and character development when used properly. It was found that the main challenge for teenagers is not the technology itself, but their ability to manage their intentions, maintain spiritual integrity, and understand that self-worth is not determined by popularity in the virtual world, but by moral character and efforts to earn God's pleasure. This study emphasizes the importance of Islamic-based digital literacy, the role of guidance from parents and educators, and the implementation of sincerity in facing changes in social media culture.